2017
DOI: 10.1136/bmj.j917
|View full text |Cite
|
Sign up to set email alerts
|

Association between trial registration and positive study findings: cross sectional study (Epidemiological Study of Randomized Trials—ESORT)

Abstract: Objective -To assess whether randomised controlled trials (RCTs) that were registered were less likely to report positive study findings compared with RCTs that were not registered and whether the association varied by funding source. Design -Cross sectional study.Study sample -All primary RCTs published in December 2012 and indexed in PubMed by November 2013. Trial registration was determined based on the report of a trial registration number in published RCTs or the identification of the trial in a search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…A recent comprehensive meta-epidemiological study reported that non-registered or retrospectively registered trials tend to show larger treatment effects [8]. Although the effect was not statistically significant, this is confirmed by cross-sectional overviews of randomized trials in cardiology [9] or general medicine [10] that report weak associations between positive findings and trial registration, although the effects were not always consistent. It is also important to note that these analyses were based on qualitative evaluations of trial results by using either a P value cut-off or the trialists' interpretation of the results in text, both of which can be problematic.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent comprehensive meta-epidemiological study reported that non-registered or retrospectively registered trials tend to show larger treatment effects [8]. Although the effect was not statistically significant, this is confirmed by cross-sectional overviews of randomized trials in cardiology [9] or general medicine [10] that report weak associations between positive findings and trial registration, although the effects were not always consistent. It is also important to note that these analyses were based on qualitative evaluations of trial results by using either a P value cut-off or the trialists' interpretation of the results in text, both of which can be problematic.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, Dechartres et al [8] found similar magnitude of bias for non-registered versus registered trials (ratio of odds ratios of 0.85)-although not statistically significant. Another cross-sectional overview of randomized trials found only a weak association between trial registration and positive study results (adjusted risk ratio of 0.87) and a possible variation between non-industry and industry funded trials [10], but concluded that evidence is inconsistent. However, it must be noted that this was a large unselected group of randomized trials across various research question and unstratified by disease, intervention, and outcome and therefore, a potentially existing effect might have been masked by the pooled analysis.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…For example, Kaplan and Irvin (43) observed a dramatic drop in the rate of positive results following the requirement to preregister primary outcomes in a sample of clinical trials. The benefits of preregistration are lost if researchers do not follow the preregistrations (44,45). However, there is evidence that preregistration makes it possible to detect and possibly correct selection and reporting biases (e.g., comparetrials.org/).…”
Section: Preregistration Distinguishes Prediction and Postdictionmentioning
confidence: 99%
“…3 15-21 For example, a study of 1122 RCTs indexed in PubMed in December 2012 found that many did not define the primary outcome (31%), state the sample size calculation (45%) or explain the method of allocation concealment (50%). 22 This lack of transparency is a major limiting factor for readers who assess an article in order to find the answer to a specific question; it is also a major problem for scientists who perform systematic reviews and meta-analyses.…”
Section: Introduction Background and Rationalementioning
confidence: 99%